Analysis of natural and technological factors of changes in exogeodynamic conditions of mine No. 2 of the Stebnytsky potassium deposit as a consequence of self-rehabilitation flooding - Yu. L. Zabulonov; Z. Z. Khevpa; I. D. Bahrii; Ia. M. Kryl; S. A. Vyzhva (Мінеральні ресурси України)
The Stebnytsy deposit of potash salts is located in the foothills of the Ukrainian Carpathians. The engineering-geological and hydrogeological conditions of the field’s operation due to the development of a thick layers of loose and water-soluble rocks are difficult of loose and water-soluble rocks are complex and therefore sensitive to mining-technological influences, extraction of rocks, deformation of the surface, hydrographic network, activation of the interaction of surface and groundwater. The most threatening situation was at mine No. 2, where in 1978, due to too intensive blasting, violation of waterproof layers, loosening and increase of water permeability, reduction of rock strength, an emergency breakthrough of super-saline waters occurred in the spent chambers of the first horizon. The total inflow of brines during the years of existence of the flow here constantly increased and reached up to 1700 m³/day, in 2002, the outflow of suprasaline waters developed in 22 points and acquired an irreversibly negative character, suffusion-diffusion processes began to develop actively. During the operation of the mine, ore extraction was carried out for a long time without laying out spent cavities, as a result of which more than 15 million m³ of unlined cavities were formed at the mine, the deformations of which disturbed the geodynamic regime of the salt-bearing massif with the subsequent development of sedimentary and karst-failure processes. In 2004, a comprehensive project for the conservation of mine No. 2 and the reclamation of disturbed lands was approved in order to restore the ecological balance in this area. Mine conservation works were carried out behind the design schedule, which led to the failure of the main provisions of the project and increased the danger due to the expansion of existing karst cavities and the formation of new ones. It can be argued that the works on the conservation of mine No. 2, including: preparation of brines, feeding them to underground mine workings, laying of chambers, etc., were carried out in a timely and incomplete manner, which does not ensure the cessation of negative consequences for the natural environment and ecological safety. The results of our research can be used in the future in the development of projects for the conservation or liquidation of salt mines.